Publisher Correction: Haze production rates in super-Earth and mini-Neptune atmosphere experiments. (April 2018) - Hörst, Sarah; He, Chao; Lewis, Nikole; Kempton, Eliza; Marley, Mark; Morley, Caroline; Moses, Julianne; Valenti, Jeff; Vuitton, Véronique
In the version of this Letter originally published Table 2, which tabulates the production rates shown in Fig. 3, was mistakenly omitted. It has now been included in all versions of the Letter.